Defining and characterising age‐friendly community pharmacies: a qualitative study. (24th April 2018) - Malet‐Larrea, Amaia; Arbillaga, Leire; Gastelurrutia, Miguel Á.; Larrañaga, Belén; Garay, Ángel; Benrimoj, Shalom I.; Oñatibia‐Astibia, Ainhoa; Goyenechea, Estíbaliz
Abstract: Introduction: The Global Network of Age‐friendly Cities is a project promoted by the World Health Organization as a response to demographic ageing and urbanization process. San Sebastian, Spain, is one of these Age‐friendly Cities and community pharmacies of the city joined the initiative. Objective: To define and implement the Age‐friendly Pharmacy concept to promote active ageing, optimize the contribution of community pharmacies of San Sebastian to the friendliness of the city and to the improvement of quality of life of the ageing population. Method: A bottom‐up participative approach was undertaken. A focus group was conducted to determine elderly people's opinions and expectations of community pharmacy. The information obtained was analysed using content analysis and validated for reliability, usefulness and applicability through three expert groups of community pharmacy owners and staff. Key findings: Fifteen requirements were agreed, covering four main areas: relationships, pharmacy layout, pharmaceutical services and communication of services. Initially, 18 community pharmacies committed to become Age‐friendly Pharmacies by pledging to these requirements and the Official Pharmacist Association of Gipuzkoa supported pharmacies in the implementation of the initiative. Conclusion: This study suggests that there is demand for a patient‐centred community pharmacy to support older people, in which pharmaceutical care services are required. The 18 Age‐friendly Pharmacies together with the Official Pharmacist Association of Gipuzkoa have publicly committed to actively work on social and patient‐centred care to meet the needs of the ageing population.